An empirical investigation on factors improving the execution of Key Performance Indicators (KPIs) for assessing the operational performance of PPP projects / Nor Suzila Lop - Lop, Nor Suzila (2021)
Public-Private Partnership (PPP) is sconceptualised as a performance-based procurement in which concessionaires are contracted to provide efficient facilities and services to the government. The quality of the facilities and services provided by the concessionaires will be assessed using key performance indicators (KPIs). This KPIs is used for determining the level of performance against the agreed level of standards as expected by the government. However, most of the PPP projects are currently facing difficulties in meeting the expectation. It is due to several issues such as lack of methods for measuring the KPIs, the lack of understanding of the KPIs implementation, project performance not reflecting the actual performance (physical) on-site, and inconsistent work performance. These shortcomings have led to the difficulty in determining the performance level of the PPP projects. Therefore, this paper aims to determine factors that facilitate in improving the implementation of KPIs for assessing the operational performance of PPP projects. The qualitative research methods using case studies via semi-structured interviews were conducted within PPP stakeholders. The data were obtained from 32 semi-structured interviews conducted across six (6) case studies university campuses. The results discovered that seven (7) factors in improving KPIs implementation for PPP projects had been determined. The determination of these factors can serve as an improved measure in assessing the PPP project performance at the operational level throughout the concession period.